Impairments in recognition of emotional facial expressions, affective prosody, and multisensory facilitation of response time in high-functioning autism - Hoffmann, Jonatan; Travers-Podmaniczky, Gabrielle; Pelzl, Michael Alexander; Brück, Carolin; Jacob, Heike; Hölz, Lea; Martinelli, Anne; Wildgruber, Dirk (Frontiers in Psychiatry, 2023)
Deficits in emotional perception are common in autistic people, but it remains unclear to which extent these perceptual impairments are linked to specific sensory modalities, specific emotions or multisensory integrationfacilitation. This study aimed to investigate uni- and bimodal perception of emotional cues as well as multisensory integration facilitation in autistic (n = 18, mean age: 36.72 years, SD: 11.36) compared to non-autistic (n = 18, mean age: 36.41 years, SD: 12.18) people using auditory, visual and audiovisual stimuli. Thereby lower identification accuracy and longer response time were revealed in high-functioning autistic people. These differences were independent of modality and emotion and showed large effect sizes (Cohen’s d 0.8 - 1.2). Furthermore, multisensory facilitation of response time was observed in non-autistic people that was absent in autistic people, whereas no differences were found in multisensory facilitation of accuracy between the two groups. These findings suggest that processing of auditory and visual components of audiovisual stimuli is carried out more separately in autistic individuals (with equivalent temporal demands required for processing of the respective unimodal cues), but still with similar relative improvement in accuracy, whereas earlier integrative multimodal merging of stimulus properties seems to occur in non-autistic individuals.